Distinct binding pattern of EZH2 and JARID2 on RNAs and DNAs in hepatocellular carcinoma development - Wen, Zhili; He, Ke; Zhan, Meixiao; Li, Yong; Liu, Fei; He, Xu; Wei, Yanli; Zhao, Wei; Zhang, Yu; Xue, Yaqiang; Xia, Yong; Wang, Fenfen; et al. (Frontiers in Oncology, 2022)
Hepatocellular carcinoma (HCC) is one of the most malignant cancers worldwide with high mortality. However, the molecular regulatory mechanisms of liver cancer, especially transcriptional and post-transcriptional mechanisms, should be further studied. Here we used chromatin and cross-linking immunoprecipitation with high throughput sequencing methods (ChIP-seq and CLIP-seq) to capture the global binding profiles on RNAs and DNAs of EZH2 and its partner JARID2 in liver carcinoma (HepG2) and normal (THLE-2) cells, respectively. We also integrated HCC transcriptome data from TCGA to analyze the expression pattern of bound genes. We found that EZH2 and JARID2 both showed distinct binging profiles between HepG2 and THLE-2 cells. By binding to the primary RNAs, bound transcripts of EZH2 and JARID2 in HepG2 showed significantly increased transcriptional level in HCC patients. The bound transcripts were also highly related to HCC development by performing gene set enrichment analysis (GSEA). We also found EZH2 and JARID2 could specially bind to several long noncoding RNAs (lncRNAs), including H19. By exploring the DNA binding profile, we detected dramatically repressed DNA binding ability of EZH2 in HepG2 cells. We also found that the EZH2-bound genes showed slightly increased transcriptional level in HepG2 cells. Integrating analysis of the RNA and DNA binding profiles suggest EZH2 and JARID2 shifts its binding ability from DNA to RNA in HepG2 cells to promote the cancer development in HCC. Our study provided a comprehensive and distinct binding profiles on RNAs and DNAs of EZH2 and JARID2 in liver cancer cell line, suggesting their potential novel functional manners to promote HCC development.